Examining commonsense epidemiology: The case of asthma. (October 2022) - Pogge, Gabrielle; Waters, Erika A; Webster, Gregory D; Fedele, David; Prabhakaran, Sreekala; Shepperd, James A
Commonsense epidemiology—how lay people think about diseases and their causes and consequences—can influence how people respond. We examined three lay epidemiological beliefs about 20 triggers and 19 symptoms among 349 caregivers of children with asthma. Our findings contradicted the prevalence-seriousness hypothesis (perceived prevalence and seriousness correlate negatively). The data partially supported the prevalence-control hypothesis (perceived prevalence and asthma control correlate negatively). We found weak support for the seriousness-control hypothesis (perceived seriousness and asthma control correlate negatively). These findings suggest boundary conditions on the application of commonsense epidemiological beliefs.